2020
DOI: 10.1002/saj2.20029
|View full text |Cite
|
Sign up to set email alerts
|

Expanding perspectives of soil nitrification to include ammonia‐oxidizing archaea and comammox bacteria

Abstract: Catalyzed by multiple groups of phylogenetically distinct microorganisms, soil nitrification impacts ground water quality, greenhouse gas emissions, and agricultural practices. This review explores known microbial players involved in nitrification, encompassing aspects of biogeography, phylogenetic diversity, physiology, and activity. We discuss distributions and activities of ammonia-oxidizing archaea and bacteria as they relate to environmental and edaphic factors and highlight a newly discovered role for te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 202 publications
1
16
0
Order By: Relevance
“…Since the discovery of comammox Nitrospira in 2015, our understanding of the two-step nitrification process has improved ( Koch et al, 2019 ; Lu et al, 2020 ; Vijayan et al, 2021 ). However, only a few comammox Nitrospira spp.…”
Section: Discussionmentioning
confidence: 99%
“…Since the discovery of comammox Nitrospira in 2015, our understanding of the two-step nitrification process has improved ( Koch et al, 2019 ; Lu et al, 2020 ; Vijayan et al, 2021 ). However, only a few comammox Nitrospira spp.…”
Section: Discussionmentioning
confidence: 99%
“…This study is focused on functionally specialized groups that have a key role in the N cycle such as ammonia-oxidizing bacteria (AOB) and ammonia-oxidizing archaea (AOA). Ammonia oxidizers perform the first and rate-limiting step of nitrification, through the oxidation of ammonia derived from both inorganic fertilization and the mineralization of organic matter (Levičnik-Höfferle et al, 2012;Lu et al, 2020). These nitrifiers exhibit niche and physiological differentiation: while low ammonium supply from mineralization of organic matter favors growth and activity of AOA, AOB prefer high ammonium supply from inorganic fertilizer inputs (Stopnišek et al, 2010;Levičnik-Höfferle et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Nitrification is a two-step process: first is the oxidation of ammonia during which the NH 4 + ion is converted into NO 2 – , and second is the oxidation of nitrite during which the NO 2 – ion is converted to NO 3 – . Ammonia oxidation can be processed by ammonia-oxidizing bacteria (AOB) (such as Nitrosomonas and Nitrosospira species of Betaproteobacteria , and Nitrosococcus species of Gammaproteobacteria ) and ammonia-oxidizing archaea (AOA) ( Hayatsu et al, 2017 ; Nacke et al, 2017 ; Lu et al, 2020 ; Lukumbuzya et al, 2020 ). Recent advances have found that AOA communities are more abundant than AOB, whereas AOB may have more functions during nitrification in the upland rice system ( Banning et al, 2015 ; He et al, 2018 ; Liang et al, 2020 ).…”
Section: Pathways Of N Cycle In Rice-based Systemsmentioning
confidence: 99%